2016
DOI: 10.1186/s13052-016-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of rituximab in treating childhood nephrotic syndrome: an Italian perspective

Abstract: BackgroundNephrotic syndrome is a disorder characterized by proteinuria, hypoalbuminemia and dyslipidemia. Low-dose alternate-day steroid regimen is the standard of care. In case of relapse or significant adverse events, steroid-sparing agents may be used. This analysis was aimed at assessing the efficacy and safety of rituximab for the treatment of children with nephrotic syndrome.ResultsFour studies were included in the final meta-analysis. The end-point of our analysis was the percentage of patients in remi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
(14 reference statements)
3
11
0
4
Order By: Relevance
“…The largest randomized placebo-controlled trial of RTX in NS administered four weekly doses of 375 mg/m 2 , reporting a median relapse-free period of 267 days in the RTX group compared to 101 days with placebo (hazard ratio 0.27, p = < 0.0001) [ 14 ]. Two meta-analyses of RTX in pediatric NS both demonstrated an improved relapse-free survival with RTX compared to other immunotherapies (relapse-free survival hazard ratio of 0.49 ( p = 0.03)) [ 26 ] and relative risk of remaining relapse-free at 6 months of 5.25, p < 0.0001) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The largest randomized placebo-controlled trial of RTX in NS administered four weekly doses of 375 mg/m 2 , reporting a median relapse-free period of 267 days in the RTX group compared to 101 days with placebo (hazard ratio 0.27, p = < 0.0001) [ 14 ]. Two meta-analyses of RTX in pediatric NS both demonstrated an improved relapse-free survival with RTX compared to other immunotherapies (relapse-free survival hazard ratio of 0.49 ( p = 0.03)) [ 26 ] and relative risk of remaining relapse-free at 6 months of 5.25, p < 0.0001) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to steroids and all immunosuppressive agents may also occur in a proportion of affected patients, and in these cases refractory steroid-resistant nephrotic syndrome, a condition with substantial risk of end-stage renal failure, has been described. Maratea et al [ 75 ] carried out an analysis aimed at assessing the efficacy and safety of rituximab, a chimeric anti-CD20 monoclonal antibody, for the treatment of children with nephrotic syndrome. The inclusion criteria of the studies were: a) a study population of children with complicated frequently relapsing/steroid-dependent nephrotic syndrome; b) the choice of rituximab as treatment; c) the choice of steroids and/or calcineurin inhibitors as control therapy; d) complete remission rate as end-point.…”
Section: Reviewmentioning
confidence: 99%
“…That study concluded significant gradual benefits for the treatment of NS by adding RTX to corticosteroid and/or calcineurin inhibitors. In safety data they collected, RTX has a limited number of adverse effects; they showed that the most common of them occurred during the infusions, but that study included only randomized control trials and is thus different from our study (1). In our investigation, some studies such as (19) clearly explained the side effects of RTX (19).…”
Section: Neutropenia=1mentioning
confidence: 59%
“…Nephrotic syndrome (NS) is a complication diagnosed by heavy proteinuria, hypoalbuminemia (serum albumin <2.5 g/dL), often associated with hypercoagulability and dyslipidemia. According to the NS clinical guidelines, for the management of children who develop frequentlyrelapsing NS (FRNS) or steroid-dependent NS (SDNS), a low-dose alternate day steroid regimen, as the first-line treatment, is prescribed (1). Long-term glucocorticoid use in FRNS/SDNS patients leads to reduced bone mineral density, hypertension, increased infection risks, comorbidities such as cushingoid habitus, growth retardation, striae and acne, cataracts, pseudotumor cerebri, impaired glucose tolerance and hypercholesterolemia (2).…”
Section: Introductionmentioning
confidence: 99%